The Impact of Earnings Management, Deferred Tax Expense and Profitability Toward Tax Avoidance - Louis Yosen Primsa Tarigan (Jurnal Penelitian Akuntansi (JPA), 2023)
Tax revenues are Indonesia's primary source of income. However, so often the realization of tax revenue did not reach the target, due to the different priorities between government and taxpayers. This study is conducted to analyze the impact of earnings management, deferred tax expense and profitability towards tax avoidance in banking companies listed on the Indonesia Stock Exchange from 2015 to 2019. The design of this study employs quantitative approach using secondary data. The research population consists of 47 banking companies, and by using purposive sampling method, the research yields 21 selected companies. Thus, the total number of samples collected from the observation period of 2015 to 2019 was 105. The research data analysis is conducted using multiple linear regression, which is processed through SPSS 25. According to the results of the research, earnings management partially does not have a significant impact towards tax avoidance, whereas deferred tax expense and profitability partially has a significant impact towards tax avoidance. Simultaneously, earnings management, deferred tax expense and profitability have a significant impact towards tax avoidance.